Impact of cardiac rehabilitation on mortality and morbidity in diabetic versus non-diabetic patients: protocol for a systematic review and meta-analysis - Linda Östlundh; Rami H Al-Rifai; Emad Hanna Dababneh; Sumanta Saha; Abderrahim Oulhaj (BMJ Open)
Background Cardiac rehabilitation (CR) decreases the morbidity and mortality risk among patients with cardiac diseases; however, the impact of CR on patients with diabetes remains underexplored. This is a protocol for a systematic review and meta-analysis methodology to explore if the effect of CR on mortality and morbidity is the same in patients with type 2 diabetes compared with patients without diabetes.Methods and analysis Interventional and non-interventional studies comparing the effect of CR, for at least 1 month, on all-cause mortality and cardiovascular outcomes including fatal and non-fatal myocardial infarction, revascularisation and rehospitalisation in adults with cardiac diseases will be deemed eligible for inclusion. Studies published between 1990 and 2020 will be searched in PubMed, Embase, Cochrane, CINAHL, Scopus and in registries for randomised controlled trials. Eligible studies will be selected using the Covidence software, and their salient details regarding the design, population, tested interventions and outcomes of interest will be gathered. The quality of studies to be deemed eligible and reviewed will be assessed using the Cochrane Collaboration and National Heart, Lung, and Blood Institute’s tools. The appraisal process will be based on the study design (interventional and non-interventional). In the meta-analysis step, the pooled effect of CR on the outcomes will be estimated. All meta-analyses will be done using the random-effects model approach (inverse-variance method). I2 and p value of χ2 statistics will guide the heterogeneity assessment. Subgroup analyses will also be performed. The small study effect will be investigated by generating the funnel plots. The symmetry of the latter will be tested by performing Egger’s test.Ethics and dissemination The systematic review will use data from published literature; hence, no ethical approval will be required. Findings of the systematic review and meta-analysis will be published in peer-reviewed international journals and will be disseminated in local and international scientific meetings.PROSPERO registration number CRD42020148832.